2016
DOI: 10.30934/kusbed.358560
|View full text |Cite
|
Sign up to set email alerts
|

Profile Of Community Mental Health Centers In Turkey Between 2013-2015 Years

Abstract: Amaç:Bu araştırma Türkiye'de 2013Türkiye'de -2015 Objectives: This study is planned to examine the profile of the Community Mental Health Centers (CMHC) in Turkey between 2013 and 2015 years. Methods: The research was structured as a descriptive study. 45 Community Mental Health Centers were included in the study (Rate of participation 42, 45%). The descriptive analysis was based on the evaluation of the data. Results

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 4 publications
0
17
0
3
Order By: Relevance
“…As a result of this, the construction of Community Mental Health Centers, under the purview of the Ministry of Health, was assured with approval number 736 on 16 February 2011 . By 2016, there were 106 of these centers across the country . CMHCs provide rehabilitation services for individuals with mental disorders, especially those with chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this, the construction of Community Mental Health Centers, under the purview of the Ministry of Health, was assured with approval number 736 on 16 February 2011 . By 2016, there were 106 of these centers across the country . CMHCs provide rehabilitation services for individuals with mental disorders, especially those with chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…CMHCs provide rehabilitation services for individuals with mental disorders, especially those with chronic conditions. These centers provide training, interviews, and counseling for patients, training and interviews for their families, occupational therapy (painting and handicraft activities), home visits, treatment and polyclinic services, sports and fairs, and music and folk dancing events with teachers from relevant fields . The aim of the CMHCs, which constitute the core of the community‐based mental health service model, is to record patients with severe mental diseases living in a specific geographical area, to provide regular follow‐up using mobile teams, to offer treatment and rehabilitation, and to help them live in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Ruhsal hastalıklara karşı damgalamayla ilgili yapılan bir çalışmada da eğitimle toplumda davranış değişikliğinin oluşturulmasını, tıp ve hemşirelik eğitiminin gözden geçirilerek psikiyatri eğitim programına bilgi, inanç ve tutum değişikliği sağlayacak özel eğitim programlarının eklenmesini, öğretmen, din adamı, basın mensubu, muhtar, sağlık personeli, polis gibi toplumun önderleri konumundaki meslek gruplarının damgalama ile mücadele hakkında eğitilmelerini ifade etmiştir (31 (32). Bilge ve arkadaşlarının yapmış olduğu bir çalışmada ülkemizde ilk TRSM sonrası bugüne kadar toplam 106 TRSM açılmıştır (33). Şizofreni hastalarının hem sosyalleşmesine hem de işlevselliklerini sürdürmesine yardımcı olan böyle derneklerin ve TRSM'lerin arttırılmasının ve hastaların buraya yönlendirilmesinin uygun olacağı düşünülmektedir.…”
Section: Discussionunclassified
“…Although many community mental health centers have been opened in our country since then, research on the functioning of the centers and the services offered has been quite inadequate (). Although a small number of studies have been going on since the first community mental health center, it is still unclear which service individuals will receive and how and by whom (Bilge et al 2016, Icel et al 2016,Söğütlü et al 2017. Bilge and colleagues (2016) in their research on the functioning of these centers, they found that one-fourth of the employees were nurses.…”
Section: In the "National Mental Health Action Plan (2011-2023)"mentioning
confidence: 99%
“…The aim of the model is to develop a meaningful, hopeful and self-determined life with a positive identity and social role (Self Recovery), by removing the patient from ongoing symptoms or disturbances and from patient role limitations (Amering and Schmolke 2012). Bilge et al (2016) found that a quarter of the employees were formed by a nurse group in their profile studies on Community Mental Health Centers. It would not be wrong to say that the group has played an important role in the quality of the services offered at these centers and will continue to play in the future.…”
Section: Application Of Recovery Model To Community Mental Healthmentioning
confidence: 99%